ASSESSMENT OF PLATELET CONCENTRATE QUALITY PARAMETERS AND CORRELATION WITH CLINICAL RESPONSE IN THROMBOCYTOPENIC PATIENTS (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Platelet transfusion is a critical therapeutic intervention for thrombocytopenic patients, yet considerable variability exists in the quality of platelet concentrates (PCs) prepared by different methods. The relationship between measurable in vitro quality parameters and actual clinical transfusion response remains insufficiently characterized, particularly in resource-constrained settings where random donor platelet concentrates (RDPs) derived from whole blood remain the predominant platelet product. Methods: A prospective observational study was conducted. A total of 540 platelet concentrate units were evaluated for quality parameters including platelet count, volume, pH, swirling, white blood cell (WBC) contamination, and sterility. Clinical transfusion response was assessed in 186 thrombocytopenic transfusion episodes using the corrected count increment (CCI) at 1-hour and 24-hour post-transfusion intervals. Results: Mean platelet yield per unit was 6.14 ± 1.42 × 10¹⁰ for PRP-PCs, 7.28 ± 1.36 × 10¹⁰ for BC-PCs, and 32.4 ± 4.8 × 10¹⁰ for SDPs (p < 0.001). The 1-hour CCI was significantly higher in patients receiving SDPs (15,840 ± 4,260) compared to pooled BC-PCs (11,620 ± 3,870) and pooled PRP-PCs (8,940 ± 3,520; p < 0.001). A significant positive correlation was observed between platelet dose per unit body surface area and 1-hour CCI (r = 0.58; p < 0.001). Satisfactory transfusion response (1-hour CCI ≥ 7,500) was achieved in 82.3% of SDP transfusions, 68.5% of BC-PC transfusions, and 51.7% of PRP-PC transfusions (p < 0.001). Conclusion: Platelet concentrates prepared by apheresis and buffy coat methods demonstrate superior in vitro quality and yield significantly better clinical transfusion responses compared to PRP-derived concentrates. Platelet dose is the strongest predictor of clinical response, underscoring the importance of quality-controlled platelet production and dose-optimized transfusion strategies.